The growth performance and physiological status of comet goldfish Carassius auratus in aquascape with different aquatic plant species - Indriani, Rafiatun; Hadiroseyani, Yani; Diatin, Iis; Nugraha, Media Fitri Isma (Jurnal Akuakultur Indonesia, 2023)
This study aimed to evaluate the growth performance and physiological status of comet goldfish (Carassius auratus) in aquascape with different aquatic plant species. Comet goldfish with average size of 6.5 ± 0.1 cm length and 9.1 ± 0.1 g weight were reared in aquascape aquarium at density of 10 fish/L for 45 days. The result of this study obtained a positive correlation between survival value and specific growth rate of the fish, followed by a significant difference value among the aquatic plant treatments compared to without aquatic plant treatments. Based on the total chromatophore cells, comet goldfish that reared in aquarium containing aquatic plants higher number of the total chromatophore cells compared to aquarium without aquatic plants. After blood glucose test, comet goldfish that reared with aquatic plants consistently showed a lower blood glucose level than without aquatic plants. The liver superoxide dismutase level of comet goldfish obtained a significant difference value between fish reared with aquatic plants and without aquatic plants, while the malondialdehyde value of all treatments was insignificantly difference. Also, the increased of total erythrocytes, total leucocytes, hemoglobin, and hematocrit were found on comet goldfish reared with aquatic plants. This study concluded that aquatic plants in rearing system can improve the survival rate, specific growth rate, and health status of comet goldfish due to mutualistic symbiosis discovered between fish and aquatic plants. Keywords: blood glucose, chromatophore cells, phytoremediation, specific growth rate, superoxide dismutase ABSTRAK Penelitian ini bertujuan untuk mengevaluasi performa pertumbuhan dan status fisiologis ikan mas komet (Carassius auratus) dalam akuaskap dengan spesies tanaman air yang berbeda. Ikan mas komet dengan ukuran rata-rata panjang 6,5 ± 0,1 cm dan berat rata-rata 9,1 ± 0,1 g dipelihara dalam akuarium akuaskap dengan kepadatan 10 ekor/L selama 45 hari. Hasil penelitian menunjukkan terdapat korelasi positif antara nilai kelangsungan hidup dan laju pertumbuhan spesifik ikan, dengan perbedaan nilai yang signifikan antara perlakuan tanaman air dibandingkan dengan tanpa perlakuan tanaman air. Berdasarkan jumlah sel kromatofor, ikan mas komet yang dipelihara dalam akuarium yang berisi tanaman air memiliki jumlah total sel kromatofor yang lebih tinggi dibandingkan dengan akuarium tanpa tanaman air. Setelah dilakukan pemeriksaan glukosa darah, ikan mas komet yang dipelihara dengan tanaman air secara konsisten menunjukkan kadar glukosa darah yang lebih rendah dibandingkan tanpa tanaman air. Kadar suproksida dismutase hati ikan mas komet diperoleh nilai perbedaan yang nyata antara ikan yang dipelihara dengan tanaman air dan tanpa tanaman air, sedangkan nilai malondialdehida pada semua perlakuan tidak berbeda nyata. Peningkatan total eritrosit, total leukosit, hemoglobin, dan hematokrit juga ditemukan pada ikan mas komet yang dipelihara dengan tanaman air. Penelitian ini menyimpulkan bahwa tanaman air dalam sistem pemeliharaan dapat meningkatkan kelangsungan hidup, laju pertumbuhan spesifik, dan status kesehatan ikan mas komet karena adanya simbiosis mutualistik yang ditemukan antara ikan dan tanaman air. Kata kunci: dismutase superoksida, fitoremediasi, glukosa darah, laju pertumbuhan spesifik, sel kromatofor